Fluid Resuscitation in Patients With Severe Burns: A Meta‐analysis of Randomized Controlled Trials. (11th November 2017) - Kao, Yuan; Loh, El‐Wui; Hsu, Chien‐Chin; Lin, Hung‐Jung; Huang, Chien‐Cheng; Chou, Yun‐Yun; Lien, Chieh‐Chun; Tam, Ka‐Wai
Abstract: Objectives: Fluid resuscitation is the mainstay treatment to reconstitute intravascular volume and maintain end‐organ perfusion in patients with severe burns. The use of a hyperosmotic or isoosmotic solution in fluid resuscitation to manage myocardial depression and increased capillary permeability during burn shock has been debated. We conducted a systematic review and meta‐analysis to compare the efficacies of hyperosmotic and isoosmotic solutions in restoring hemodynamic stability after burn injuries. Methods: PubMed, Embase, Cochrane Library, Scopus, and ClinicalTrials.gov registry were searched. Randomized control trials evaluating the efficacy and safety of hyperosmotic and isoosmotic fluid resuscitation in patients with burn injuries were selected. Eligible trials were abstracted and assessed for the risk of bias by two reviewers and results of hemodynamic indicators in the included trials were analyzed. Results: Ten trials including 502 participants were published between 1983 and 2013. Compared with isoosmotic group, the hyperosmotic group exhibited a significant decrease in the fluid load (vol/% total body surface area [TBSA]/weight) at 24 hours postinjury, with a mean difference of −0.54 (95% confidence interval = −0.92 to −0.17). No differences were observed in the urine output, creatinine level, and mortality at 24 hours postinjury between groups. Conclusions: Hyperosmotic fluid resuscitation appears to be an attractive choice for severe burns in terms of TBSA or burn depth. Further investigation is recommended before conclusive recommendation.